Prevalence of Metabolic Syndrome in Vitiligo Patients and its Relation to Vitiligo Severity - A Cross-Sectional Study - Navya Bathina; Sadhika Ganni; Seetharam A. Kolalapudi; Subhashini Konala; Kalyan Dharavath; Mandem T. K. Reddy (Wolters Kluwer Medknow Publications, 2024)
Background: In vitiligo, there is a significant decrease in melanocytes and melanin. The decrease in melanin causes oxidative stress, with a chance of causing metabolic syndrome. Hence, there is a need to look for metabolic syndrome in vitiligo. Aim and Objectives: To estimate the prevalence of metabolic syndrome in vitiligo patients and to evaluate the relationship between the severity and progression of vitiligo and metabolic syndrome. Materials and Methods: A hospital-based cross-sectional study was conducted on 178 vitiligo cases and 178 controls who were age- and sex-matched. The type of vitiligo, stability by vitiligo disease activity score (VIDA), and severity by vitiligo area severity index (VASI) were noted. The waist circumference, blood pressure, fasting lipid profile, and fasting blood sugar were measured for cases and controls. Metabolic syndrome was diagnosed based on Harmonization Asian criteria. Results: The mean age in cases was 34.38 years, and in controls, it was 35.67 years. The majority were females in both cases (52.2%) and controls (55.6%). Most have a VIDA score of 2+ (41.6%). The mean VASI score was 2.54. The percentage of metabolic syndrome was higher in cases (36%) compared to controls (24.2%) (P = 0.015). The mean age was lower in vitiligo cases with metabolic syndrome (38.83 years) compared to controls with metabolic syndrome (43.14 years). Metabolic syndrome was more frequent in the vitiligo vulgaris type (48.9%) than in acral and segmental vitiligo. Metabolic syndrome was more common in patients with high VIDA (45%) and VASI (52.3%) scores compared to patients with low VIDA (25%) and VASI (27.3%) scores. Limitation: It is a hospital-based study, so controls were not from the general population. Conclusion: The prevalence of metabolic syndrome was higher in vitiligo patients compared to controls, and it was higher in patients with active and severe disease. Screening and close monitoring of vitiligo patients help in the early diagnosis of metabolic syndrome and reduce the risk of cardiovascular disease.